Proposal of numerical models to predict the diffuse field sound absorption of finite sized porous materials – BEM and FEM approaches. (September 2021) - Pereira, M.; Mareze, P.H.; Godinho, L.; Amado-Mendes, P.; Ramis, J.
Abstract: The prediction of the sound absorption coefficient in diffuse field conditions is of great interest to an acoustic project. Foams and granular materials like porous concrete have been used in many internal or external applications as sound absorbers. However, many doubts have regularly been discussed in scientific literature. The simple use of experimental impedance tube methods, that consider only the incident acoustic plane waves, is not equivalent to the experimental measurement in a reverberant room, which is necessary for a correct characterization of a given constructive solution. The scientific community has explored several methods to predict and approximate the sound absorption coefficient in diffuse field conditions, using only acoustic plane wave data. However, many of them do not allow a realistic approximation of the reverberant room measured data. Therefore, two numerical models are herein proposed which consider the porous media on the fluid-equivalent theory, first, a two-dimensional (2D) finite element method, and, second, a three-dimensional (3D) boundary element method (BEM). These methods are compared with analytical equations and experimental data from the reverberant room, studying the influence of the porous material panel size in the sound absorption coefficient in diffuse field conditions. To illustrate the proposed method's practical interest, the BEM 3D model was used to determine the diffuse field's sound absorption coefficient for finite-sized panels of porous concrete. This test was done for plane panels and for slit-like surfaces to highlight the possibilities of the proposed method.